Fiber Plastic Composite made from Old Corrugated Paper and Polyprophylene (PP) with Addition of Maleic Anhydride (MAH) and Benzoil Peroxide (BP) - Nova Tampubolon; Luthfi Hakim; Tito Sucipto (Program studi Kehutanan USU, 2013)
The research of using old corrugated paper fiber and used recycled polyprophylene plastic ore as the raw material of making fiber plastic composite board was useful to give solution the waste problem. The purpose of research was to evaluate physical properties (density, moisture content, water absorbtion, thickness swelling) and mechanical properties (modulus of elasticity, modulus of rupture, internal bond, screw holding power)fiber plastic composite board with maleic anhydride (5% and 7%) as compatilizer and benxzoil peroxide (15%) as initiator. The composition raw materials and matrics was useful 50:50, 60:40, 70:30 with 3 replication and 25 cm x 20 cm x 1 cm for the dimention and density target 0.8 g/cm3. The raw material was made become pellet by using extruder at 100-1700C. The board were hot press 170-1800C and conditioned for 1 weeks, to evaluate physical and mechanical properties were carried out according to JIS A 5905-2003 hardboard S20 dan JIS A 5908 (2003) particleboards type 13. The result of the research showed that physical of fiber plastic composite board did not fulfill the standard of JIS A 5905-2003 hardboard S20, except density. The testing of mechanical properties by MOR, IB and KPS was fulfill standar JIS A 5905-2003 hardboard S20 dan JIS A 5908 (2003) particleboards type 13. Standard JIS A 5908-2003 S20 hardboard full value in testing physical properties, namely the density testing, while in the testing of mechanical properties, namely the testing of MOR. Fiber plastic composite board suitable for using exterior and interior. Based on physis and mechanical properties testing, the best value of fiber plastic composite was composition 30:70 MAH 5%. Keyword: old corrugated paper, used recycled polyprophylene plastic ore, MAH and BP, FPC board, physiscal and mechanical properties.